Os perpétuos e os incompletos: permanência e movimento nos gibis de super-heróis e na série Sandman - Pereira, Luís Fernando dos Reis (2010)
This thesis analyzes the fictional narratives of the comics books series Sandman, written by the British author Neil Gaiman, originally published by DC Comics and, in Brazil, by Globo, from 1989 to 1996, noting the translation and appropriation of elements from different cultural contexts for the construction of the narrative, in order to demonstrate that Sandman has a higher tendency to mobility and articulation than the superhero s comic books, which generally emphasize the structures of permanence and isolation. We investigate how the principle of identity, developed by certain core of Western thought is used, as well as different characteristics from other cultural backgrounds, bringing into play concepts such as centrality and periphery, reality/fiction, stability/instability, etc. In support of our journey, we turn to theories about the processes and semiotic systems of culture, exploring and articulating studies of Yuri Lotman, Severo Sarduy, Amálio Pinheiro, Jesus Martín-Barbero and Edgar Morin, while the theories of Scott McCloud and Will Eisner served as basis for studying the recent and still in process language of the "comics" as art and media; we counted, as well, with the major contributions of Bakhtin s theories of novel and literary genres carnavalization, to support aspects of narrative language on the studied comics. The Sandman series, with 75 editions and some special publications, combines aspects of the American superhero comics, mythology, pop culture, literature, religion, paganism, magic, fantasy, gothic horror, historical facts, philosophical references, elements of the classic epic and folklore to tell the story of Dream, also called Oneiros, Morpheus, etc., ruler of the Dreaming, and their complex relations with humanity and other beings, including his siblings Destiny, Death, Destruction, Desire, Despair and Delirium; modern gods and those who have been forgotten; their mortal and immortal lovers; Lucifer and his demons; and even the angels. In the periphery of such a mosaic plot, perverting the classic epic elements, remnants of the drama of a missing hero, unfinished and absurd, unable to remain equal to himself, and who insists in to inhabit different borders: islands between reality and the Dreaming; soft regions where time becomes malleable (local of translations between the familiar and the foreign), and his own kingdom, which is a metaphorical border between life and death. Such arrangements allow the discussion of the signic operating environment proposed by Lotman, the semiosphere, and its mobile/translation borders, a key concept to understanding the trends of permanence and change of the cultural texts Finally, Dream, occasional actor, the personification of the dream itself, questions, over the stories, the objective notions of identity, truth and immutability, as well as we may question, similarly, the principle of identity in self-centered and self-referencing cultures based on binary logic and mainly closed systems that tend to generate several ways of exclusion, through the idea of truth and tolerance, unlike the Sandman s realm environments, linked to Derrida's discussion of the idea of hospitality